5-aminolevulinic acid guidance during awake craniotomy to maximise extent of safe resection of glioblastoma multiforme. (15th July 2015) - Corns, Robert; Mukherjee, Soumya; Johansen, Anja; Sivakumar, Gnanamurthy
Abstract : Overall survival for patients with glioblastoma multiforme (GBM) has been consistently shown to improve when the surgeon achieves a gross total resection of the tumour. It has also been demonstrated that surgical adjuncts such as 5-aminolevulinic acid (5-ALA) fluorescence—which delineates malignant tumour tissue— normal brain tissue margin seen using violet-blue excitation under an operating microscope—helps achieve this. We describe the case of a patient with recurrent left frontal GBM encroaching on Broca's area (eloquent brain). Gross total resection of the tumour was achieved by combining two techniques, awake resection to prevent damage to eloquent brain and 5-ALA fluorescence guidance to maximise the extent of tumour resection.This technique led to gross total resection of all T1-enhancing tumour with the avoidance of neurological deficit. The authors recommend this technique in patients when awake surgery can be tolerated and gross total resection is the aim of surgery.